Modelling α-synuclein processing in primary patient cells for pharmacological intervention - Jessica K. Smith; George D. Mellick; Alex M. Sykes (Open Exploration Publishing Inc., 2023)
Aim: Parkinson's disease (PD) is a complex, chronic neurodegenerative disorder with predominately sporadic etiology. Intricate genetic-environmental interactions lead to the hallmarks of the disease: degeneration of dopaminergic neurons and the deposition of α-synuclein aggregates. The aim of this study was to establish a novel primary patient cell model as an in vitro screen to study α-synuclein processing for drug screening. Methods: Primary patient olfactory neuroepithelial-derived cells (ONS) were exposed to α-synuclein and examined for cytotoxicity, processing, and solubility over 48 h. Epigallocatechin gallate (EGCG), which is known to destabilise α-synuclein fibrils, was used to investigate the solubilisation of α-synuclein in the model system. Results: Exposure to 0.1 μmol/L α-synuclein preformed fibrils was not toxic to ONS over 48 h. ONS processing of α-synuclein was observed to be different in PD cells by their increased accumulation in the cytoplasm. Processing deficits in the PD ONS were confirmed by immunoblotting with an increase in sodium dodecyl sulfate (SDS)-insoluble α-synuclein after 48 h. Conclusions: The data has illustrated the utility of primary patient ONS as a model system to understand the processing of α-synuclein. Considerable differences in α-synuclein processing were identified in PD ONS. Furthermore, the data suggests that primary patient ONS are a viable in vitro drug screening platform for α-synuclein pathology in PD.